2004
DOI: 10.1074/jbc.m406548200
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Strength and Transition Metals Control PrPSc Protease Resistance and Conversion-inducing Activity

Abstract: The essential component of infectious prions is a misfolded protein termed PrPSc , which is produced by conformational change of a normal host protein, PrP C . It is currently unknown whether PrP Sc molecules exist in a unique conformation or whether they are able to undergo additional conformational changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 77 publications
2
32
0
2
Order By: Relevance
“…In contrast, previous studies using cell-free conversion 6 and rPrP fibril formation [7][8][9] , respectively, in the presence of denaturant or at low pH have shown that the rate of PrP-res formation was directly proportional to the PrP-sen concentration, presumably owing to the homogenous denaturation status of on QUIC reactions showed that salt is needed for rPrP-res formation and the sensitivity of this method was maximal at 500 mM NaCl at pH7. The requirement for salt in rPrP-res formation is consistent with the fact that salt is required for cell-free conversion in the absence of GdnHCl 10 and the maintenance of a protease-resistant PrP Sc conformation 11 . In addition, salt has also been reported to reduce the thermodynamic stability of the rHuPrP-sen 12 .…”
Section: Acknowledgmentsmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, previous studies using cell-free conversion 6 and rPrP fibril formation [7][8][9] , respectively, in the presence of denaturant or at low pH have shown that the rate of PrP-res formation was directly proportional to the PrP-sen concentration, presumably owing to the homogenous denaturation status of on QUIC reactions showed that salt is needed for rPrP-res formation and the sensitivity of this method was maximal at 500 mM NaCl at pH7. The requirement for salt in rPrP-res formation is consistent with the fact that salt is required for cell-free conversion in the absence of GdnHCl 10 and the maintenance of a protease-resistant PrP Sc conformation 11 . In addition, salt has also been reported to reduce the thermodynamic stability of the rHuPrP-sen 12 .…”
Section: Acknowledgmentsmentioning
confidence: 58%
“…Shaking is thought to cause partial unfolding of a portion of the rPrP-sen by increasing the air-water interface 11 . Moreover, shaking enhances the interaction between rPrP-sen and PrP Sc , and promote the fragmentation of rPrP-res polymers 12 .…”
mentioning
confidence: 99%
“…An NMR structure of the octapeptide repeat from residues 61 to 84 bound to pentosan polysulfate was recently released showing a series of loosely defined loops with hydrophobic exposed tryptophans (Taubner et al, 2009). Interestingly, Cu may also influence the protease resistance of PrP Sc molecules (Nishina et al, 2004), and PrP Sc formed in a Cu-free environment was 20 times more susceptible to proteinase-K digestion; addition of Cu restored normal protease resistance.…”
Section: Metal Ionsmentioning
confidence: 99%
“…The conversion process is enhanced by RNA molecules, redox-active metals like copper, certain denaturants, sulfated glycans, solvents, pH, temperature, reducing agents, inhibition of glycosylation, and a combination of buffer conditions and metal ions (156,197,246 (43,79,136). However, astrocyte-specific expression of PrP C is sufficient to support the replication and neurotoxicity of infectious PrP Sc , even in the absence of neuronal PrP C expression, indicating the involvement of other neurotoxic molecules or mechanisms in this process (98).…”
Section: Deposits Of Prpmentioning
confidence: 99%
“…The majority of these metals induce the aggregation of purified or recombinant PrP C to a form resembling PrP Sc in certain characteristics (156). How- …”
Section: B Prp and Other Metals In Particular Ironmentioning
confidence: 99%